2017
DOI: 10.1590/1413-81232017222.09422016
|View full text |Cite
|
Sign up to set email alerts
|

Padrões alimentares de escolares: existem diferenças entre crianças e adolescentes?

Abstract: (23.3%; n = 147), "restricted" (22.7%; n = 143), "healthy" (22.0%; n = 139), "Brazilian processed" (17.4%; n = 110) and "mixed" (14.5%; n = 92). The healthy pattern was positively associated to lower age (< 10 years, children)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
21

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 28 publications
0
18
0
21
Order By: Relevance
“…Recently, in Polish adolescents from less urbanized regions, it was shown that rural residence was not a barrier to a well-composed diet [60]. Similarly, no impact of place of residence on dietary patterns in children from public schools in Brazil was observed [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, in Polish adolescents from less urbanized regions, it was shown that rural residence was not a barrier to a well-composed diet [60]. Similarly, no impact of place of residence on dietary patterns in children from public schools in Brazil was observed [24].…”
Section: Discussionmentioning
confidence: 99%
“…There have been several studies focused on the clustering of dietary-related and lifestyle-related behaviours in teenagers [2,10,13,14,15,16,17,18,19,20,21,22,23,24]. Two main patterns, one described as an ‘active and healthy lifestyle’ and the opposite as a ‘high screen time and unhealthy lifestyle’, were reported in school-age children from Spain [14], Finland [15] and nine European countries [25].…”
Section: Introductionmentioning
confidence: 99%
“…The consumption of processed foods, including soft drinks (such as soda), and treats (candies, chewing gums, chocolates etc. ), is considerable among students in Brazil [12][13][14], especially among adolescents [15]. These foods are considered as "ultraprocessed" by the Food Guide for the Brazilian Population, whose nutritional composition is unbalanced, favoring the excessive consumption of calories and the substitution of in natura or minimally processed foods.…”
Section: Discussionmentioning
confidence: 99%
“…Em estudo realizado por Corrêa et al (2017), no qual foram analisados padrões alimentares de escolares, obteve-se o percentual de 22,7% (n=143), caracterizado como padrão alimentar saudável. Dentro do padrão saudável foi incluído o consumo dos seguintes alimentos: saladas, legumes e verduras cozidos; frutas; feijão; leite/iogurte.…”
Section: Página |unclassified